Carbon-Based Metal Free Catalysts : Preparation, Structural and Morphological Property and Application - Abdullah Mohammed, Ahmed Asiri (Elsevier, 2022)
Carbon-Based Metal Free Catalysts: Preparation, Structural and Morphological Property and Application covers the dierent aspects of carbon-based metal free catalysts, including the fabrication of catalysts from natural sources and carbon allotropes, their manufacturing and design, characterization techniques, and applications. Special features in the book include illustrations and tables which summarize up-to-date information on research carried out on manufacturing, design, characterization and applications of metal free catalysts. This book assembles the information and knowledge on metal free catalysts and emphasizes the concept of green technology in the eld of manufacturing and design. It is an ideal reference source for lecturers, students, researchers and industrialists working in the eld of new catalyst development, especially polymer composites and is a valuable reference book handbook for teaching, learning, and research.